Strategizing global health governance: unpacking opportunities and challenges for least developed nations within the WHO pandemic treaty framework - Jiang, Shisong; Kumah, Emmanuel (Frontiers in Public Health, 2023)
Exploring the intricacies of the proposed WHO pandemic treaty, this paper underscores its potential benefits and challenges for Least Developed Nations (LDNs) in the global health landscape. While the treaty could elevate LDNs' access to vital resources, fortify health systems, and amplify their voice in global health governance, tangible challenges in safeguarding equitable access, protecting sovereignty, and ensuring compliance are illuminated. Concluding with targeted recommendations, the paper advocates for treaty revisions that assure resource access, safeguard LDNs' autonomy, and foster capacity-building. In essence, the paper emphasizes the imperative of genuinely empowering LDNs, crafting a pandemic treaty that establishes a more equitable, resilient, and inclusive global health future.